Mountain & Alpine Medicine - Faulhaber M; 3; Pocecco E; 2; Posch M; Ruedl G (Deutsche Zeitschrift für Sportmedizin, 2020)
This article presents epidemiological data on traumatic accidents during mountain hiking in the summer season and recreational alpine skiing in the Austrian Alps.In mountain hiking, the absolute number of fatalities remained stable from 2006-2014 (32 to 46 victims per year), whereas the number of non-fatal accidents increased by about 5% per year implying a decreasing mortality index. About 75% of all falls happened during the descent and 70% of the victims who sustained a fall-related injury showed defective vision. Mountain hikers should pay attention to sufficient regeneration before and breaks during descending. Additionally, a regular check of visual aids (glasses, contact lenses) can be recommended.In recreational alpine skiing, the injury rate is estimated to be less than 1 injury per 1000 skier days and the traumatic fatality rate amounts to 0.36 traumatic deaths per million skier days. A tear of the anterior cruciate ligament is the most common diagnosis with about 15-21% of all injuries and the risk is 3 times higher in women than in men. Protective equipment and an appropriate skiing speed, depending on skill level, represent preventive measures to reduce injuries and traumatic deaths.Key Words: Traumatic Accidents,Falls, Injuries, Anterior Cruciate Ligament